Solve x2 + 12x = –11 by completing the square. Which is the solution set of the equation?

Answers

Answer 1
Answer: If you would like to solve the equation x^2 + 12 * x = -11, you can calculate this using the following steps:

x^2 + 12 * x = -11
x^2 + 12 * x + 11 = 0
(x + 1) * (x + 11) = 0
1. x = - 1
2. x = - 11

The correct result would be x = - 1, or x = - 11.

Related Questions

We have:a,b,c are natural prime numbers and What are the numbers? Without using GUESS-WORK!
What is the largest factor of 16 that is also a perfect cube?
Simplify the expression. 12^–3 • 12^10 • 12^0A. 1 B. 1728^7 C. 12^7 D. 36^7
Express 15% as a fraction
How do you simplify (1/x+h) - (1/x)

Ashley deposits $1000 into an account that earns 4% interest compounded 2 times per year. how much money will Ashley have in her account after 5 years? round to the nearest cent A)1520.30
B)1892.19
C)1218.99
D)1253.00

Answers

The equation for compound interest is A=P(1+(r)/(n))^(nt), where:
P is the original deposit (or "principal")
r is the rate of the interest (in decimal form)
n is the number of times per year that the interest is compounded
t is the time passed in years

Plugging in your values, we see that the equation becomes A=1000(1+(.04)/(2))^((2)(5))=1000(1.02)^(10)

which equals, to the nearest cent, $1218.99, which is answer C.


what would be an outlier if added to the data set below? 507, 586, 499, 542, 615, 600, 561, 519 A.487 B.535 C.610 D.380

Answers

I am pretty sure the answer is F

How do I solve for the equation s=3f-24? Solve for f

Answers

s-3f=-24
-3f=-24-s
3f=24+s
f=24+s/3

Final answer:

To solve for 'f' in the algebraic equation 's=3f-24', add 24 to 's' and then divide the result by 3.

Explanation:

To solve the algebraic equation 's=3f-24' for 'f', you would first decide to isolate 'f'. To do this, start by getting rid of the '-24' on the right side of the equation by adding 24 to both sides. This would simplify the equation to 's+24=3f'. Next, divide both sides of the equation by 3. This step will result in a final solution of 'f=(s+24)/3'. So, to solve for 'f' in the provided equation, simply add 24 to the original 's' value and then divide the result by 3.

Learn more about Algebra here:

brainly.com/question/32436021

#SPJ2

the area of a rectangular pool is given by the trinomial to 2y^2+y - 3 what are the possible dimensions of a pool. use factoring

Answers

2y² + y - 3

(2y+3)(y-1)

2y(y-1) + 3(y-1)
2y² - 2y + 3y - 3
2y² + y - 3

2y + 3 = 0
2y = -3
y = -3/2
y = -1 1/2

y - 1 = 0
y = 1

2y² + y - 3 = 0
2(-3/2)² + (-3/2) - 3 = 0
2(9/4) - 3/2 - 3 = 0
18/4 - 3/2 - 3 = 0
18/4 - (3/2 * 2/2) - 3(4/4) = 0
18/4 - 6/4 - 12/4 = 0
(18 - 6 - 12)/4 = 0
(18 -18)/4 = 0
0/4 = 0
0 = 0



Answer:

(y+1)(2y−3)

Step-by-step explanation:

Which shows 60^2 − 40^2 being evaluated using the difference of squares method?(A)60^2-40^2=(3600+1600)(3600-1600)=10,400,000
(B)6^2-40^2=3600-1600=2,000
(C)60^2-40^2=(60-40)^2=20^2=400
(D)60^2-40^2=(60+40)(60-40)=(100)(20)=2,000

Answers

Answer:

Option D - 60^2-40^2=(60+40)(60-40)=(100)(20)=2000

Step-by-step explanation:

Given : Expression  60^2-40^2

To find : Which shows expression being evaluated using the difference of squares method?

Solution :

The best method to find the difference of squares method is by using identity,

a^2-b^2=(a+b)(a-b)

According to question,

a=60 and b=40

60^2-40^2=(60+40)(60-40)

60^2-40^2=(100)(20)

60^2-40^2=2000

Therefore, Option D is correct.

D. The answer has to be 2,000, eliminating A and C. B doesn't even use the original equation, as well as incorrectly solving the method, so D is the correct answer, even if you don't understand the principles.

Foil Multiplication (2n+4)•(4n+7)

Answers

(2n+4)x(4n+7)

=  8n^2+14x+16n+28
=8n^2+30n+28 

that's it :) !! 


Step 1: 8n+14n+12n+28

Step 2 Combine like terms: 8n+26+28

Final Answer: 34n+28